Effect of auxins on growth enhancement of cell suspension culture of Tongkat Ali Hitam (Polyalthia bullata) - Farezol, Nurul Farhana; Kamarul Zaman, Munirah Adibah; Mohamad Azzeme, Azzreena (Persatuan Biologi Gunaan Malaysia, 2024)
Polyalthia bullata, a Southeast Asian plant, is valued for its bioactive compounds with pharmaceutical potential. To prevent overharvesting and extinction, cell suspension culture offers a sustainable method for the mass production of these compounds. Despite its effectiveness, no studies on Polyalthia bullata cell suspension culture have been established. Therefore, this study aimed to establish the culture by evaluating growth and biomass production. To achieve the objective, leaf derived callus of Polyalthia bullata was multiplied on Murashige and Skoog (MS) + 30 µM dicamba medium. Subsequently, cell suspension initiation and multiplication were carried out using half-strength MS basal medium (½ MSO) supplemented with 5, 15, 25, and 30 µM of 1-naphthaleneacetic acid (NAA), indole-3-acetic acid (IAA), and indole-3-butyric acid (IBA), respectively. In this study, suspension cells in the ½ MSO recorded the highest increment in fresh (4.455 ± 1.170 g FW) and dry weight (0.220 ± 0.033 g DW) but produced dark brown cells. Meanwhile, cells grown on ½ MS medium supplemented with 30 µM NAA recorded the highest increase in fresh weight (3.472 ± 0.694 g FW) and dry weight (0.190 ± 0.012 g DW), displaying a light yellowish-brown cell. Although the ½ MSO yielded the highest biomass, the cell suspension cultures supplemented with 30 µM NAA showed promising results, achieving higher biomass compared to other auxin treatments and exhibiting a light yellowish-brown cell. This suggests that 30 µM NAA is a more efficient auxin utilization in reducing the occurrence of dark brown cells. In conclusion, optimizing auxin concentrations is crucial for high-quality Polyalthia bullata cell suspension culture. This study can provide insight into sustainable cultivation practices for the plant, serving as a potential bio-factory for mass-producing bioactive compounds.